Prevention of Violent Behavior in Early Childhood Through Legal Protection in the Community Environment - Novi Cynthia Yusnita; Afdhalina, Afdhalina; A. Zebar; Junaidi Lubis (Jurnal Multidisiplin Sahombu, 2025)
Violence against early childhood is not only limited to physical acts such as hitting, slapping, or directly hurting, but also includes verbal, emotional, sexual violence, and neglect of children's rights. This study aims to provide information and insight regarding legal protection against violence against early childhood. This study uses library research by analyzing journals, books and the Constitution to analyze problems related to violence against early childhood. The results of this study indicate that there are several documents on legal protection for children such as constitution No. 35 of 2003 concerning Child Protection, constitution No. 20 of 2003 concerning the National Education System, Law No. 23 of 2004 concerning the Elimination of Domestic Violence, the Criminal Code and the Law Concerning Criminal Violence against Children. Although normatively legal protection for early childhood is quite adequate, its implementation still faces many obstacles. Synergy is needed between law enforcement officers, child protection agencies, the community, and the government to create a safe and child-friendly environment.